Design thinking and innovation in learning - Taricani, Ellen (Emerald points., 2021)
Acknowledging that empowering today's learner to find innovative and enriching experiences brings about a deeper desire within them to learn and develop skills, this book showcases a combination of innovative educational practices and creative pedagogy techniques to demonstrate how educators can kick-start learning success. Serving up chapters that cross cultural boundaries and present numerous possibilities to assist in constructing new ventures in the classroom, the authors demonstrate how innovation in education and educational policies create new pathways and partnerships for educators. With each author offering a unique perspective on innovative teaching and learning, they chronicle their successes and failures, present new possibilities for enacting practical change in the classroom, and document how the impact of change is experienced and modified as successful techniques are implemented. Collectively, the chapters shine a light on the power of exposure to diverse opportunities, access to multiple techniques, and cross-cultural functionality in providing expansive value to the learner. Appealing to researchers interested in digital storytelling, blended learning, academic integrity, design thinking methods and educational collaboration, this edited collection emphasises the role of innovative educational design in framing and developing global leaders and mobilizing significant change.